Social Adaptation of Athletes in Ukraine: Challenges and Priority Areas of Support - Bulatova, Mariia; Radchenko, Lidiia; Pryimak, Mariia (Physical Education Theory and Methodology, 2025)
Background. Sport represents a crucial component of human life, yet the intensity of training, coupled with significant physical and psycho-emotional strain, often restricts athletes’ opportunities for holistic personal development and limits their integration into the social environment. These challenges become especially acute during the transition from active competitive activity to the post-career stage. Objectives. This study aimed to conduct a comprehensive analysis of the level of awareness among specialists in the field of physical culture and sport regarding the concept of athletes’ social adaptation and to identify the key problems athletes encounter throughout this process. Materials and Methods. The study was based on an anonymous online survey involving 150 specialists representing diverse sectors of the field of physical culture and sport in Ukraine. A set of complementary methods was employed, including system analysis, analysis and synthesis of scientific literature, sociological survey, and statistical analysis, using the chi-square (χ²) test to assess the relationship between professional experience and awareness levels. Results. The findings indicate that 87.3% of respondents considered the social adaptation of athletes to be “undoubtedly very important”. The most critical challenges during athletes’ professional careers were identified as the imbalance between sport and education (54.5%) and psychological overload and stress (40.0%). In the post-career stage, the leading difficulties were related to employment (33.8%) and financial instability (26.9%). The most effective forms of post-career support were recognized as employment assistance (mean score = 4.3) and financial support (mean score = 4.0). At the same time, the primary barriers to implementing adaptation programs included insufficient funding (37.3%) and athletes’ limited awareness of available opportunities (19.3%). Conclusions. The study underscores the urgency of developing and institutionalizing comprehensive national programs for the social adaptation of athletes in Ukraine, ensuring their continuity across all career stages.